2006
DOI: 10.1111/j.1460-9592.2005.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric anesthesia practice and training in Japan: a survey

Abstract: This survey revealed that although pediatric anesthesia training is considered mandatory, university hospitals lack adequate numbers of pediatric cases and children's hospitals suffer from a shortage of staff positions and anesthesiologists, and hence are unable to satisfy this demand. Most representative members of our society consider it too early to subspecialize pediatric anesthesia in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Many Schools of Anaesthesia in Italy require a minimum number of procedures to be performed by trainees during the training period (25-100 procedures). A survey conducted by Shimada et al revealed that there was no special pediatric anesthesia training program in 49 out of 70 University Hospitals in Japan (14). Based on their survey in 2003, they have recommended a training period of 6 months in a Children's Hospital or 100 anesthetics for children <6 years of age as a prerequisite for board qualification in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Many Schools of Anaesthesia in Italy require a minimum number of procedures to be performed by trainees during the training period (25-100 procedures). A survey conducted by Shimada et al revealed that there was no special pediatric anesthesia training program in 49 out of 70 University Hospitals in Japan (14). Based on their survey in 2003, they have recommended a training period of 6 months in a Children's Hospital or 100 anesthetics for children <6 years of age as a prerequisite for board qualification in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, an interesting survey about pediatric anesthesia training in Japan has been published by Shimada et al. (8). As with other guidelines, the Japanese Society of Anesthesiologists Committee on Education has published educational guidelines for anesthesia board qualification, according to which pediatric anesthesia will become in the near future, one of the major educational prerequisites for qualification.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, training in pediatric anesthesia was evaluated by Shimada and colleagues, who reported that only a very low percentage of interviewees practiced pediatric anesthesia daily, while many did not practice it at all. These poor results are likely due to the fact that almost all anesthesia schools did not provide specific pediatric training, even if it was considered mandatory by the Japanese Society of Anesthesiologists [20].…”
Section: International Perspectivementioning
confidence: 99%